Study of antiviral and virucidal activities of aqueous extract of Baccharis articulata against Herpes suis virus - Torres, Cristina Vanesa (2011)
Baccharis articulata is native of América and traditionally used for the treatment of digestive disorders and urinary infections. Cytotoxicity of aqueous extracts of B. articulata was investigated in Vero cells. As the maximal non cytotoxic concentration has been established, this concentration has been used to evaluate antiviral and virucidal activities against Herpes suis virus type 1, member of the same subfamily of Herpes simplex virus. Aqueous extracts of B. articulata exhibited more than 95% of virucidal activity. These findings support their potential application as a disinfectant or antiseptic with low toxicity and provide a valuable knowledge to ethnopharmacology properties of Baccharis articulata.